Employee Turnover in Automotive Retail: The Role of Mindset, Motivation, and Work Environment - Joice LP Nahumury; Ani Solihat (Mandalika Institute, 2026)
High employee turnover has become a critical challenge threatening the sustainability of automotive retail companies in Indonesia. This study examines employee turnover in an automotive retail company in South Tangerang that recorded an 80% turnover rate during the first semester of 2025. Unlike previous studies that tend to analyze turnover determinants separately, this research integrates mindset, work motivation, and work environment within a single analytical framework to provide a more comprehensive understanding of turnover behavior. A qualitative approach with a single case study design was employed. Data were collected through semi-structured interviews with 15 purposively selected informants, non-participant observation, and documentation studies. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña (2014). The findings indicate that: (1) a dominant fixed mindset reduced employees’ psychological resilience in coping with work pressure; (2) motivational deficits resulting from uncompetitive compensation and limited recognition strengthened turnover intention; and (3) an unconducive work environment weakened employees’ affective commitment to the organization. These factors interacted synergistically in shaping turnover behavior. The study recommends holistic interventions through growth mindset development, compensation restructuring, and improvements in organizational climate to enhance employee retention.